Governance Challenges for Implementing Nature-Based Solutions in the Asian Region - Morita, Kanako (2021)
Nature-based solutions (NbS) are recognized under the United Nations Framework Convention on Climate Change and the Convention on Biological Diversity. This relatively new concept has become a key element in strategies for green recovery from the Covid-19 pandemic. NbS consist of a range of measures that address various societal challenges, including climate change, natural disasters, and water security, by combining human well-being and biodiversity benefits. Although the importance of NbS has been widely recognized, existing studies on aspects of their governance are limited and mainly focus on NbS in European countries. There is little relevant research in other regions, including Asia. This study aimed to explore challenges for NbS governance by analyzing the development and implementation of NbS in Asia. We focused on NbS in the fields of climate change mitigation and adaptation, disaster risk reduction, and infrastructure. In these three fields, NbS are linked to climate security issues and have been widely implemented in Asian countries. This analysis identified the challenges for NbS governance for countries at different stages of economic development, and for developing measures for NbS with different institutions and actors. It recognizes the importance of a framework that matches the need for NbS with relevant institutions and actors at various scales and in various sectors. Guidelines are required to integrate NbS into strategies and policies at national and local levels and also into international cooperation.